2021
DOI: 10.1557/s43580-021-00134-w
|View full text |Cite
|
Sign up to set email alerts
|

Starch from Ramon seed (Brosimum alicastrum) obtained by two extraction methods

Abstract: Brosimum alicastrum is a native tree widely distributed in the Yucatan peninsula where is called Ramon. Some studies have reported that Ramon seeds contain high starch content, recently used in developing novel and sustainable biomaterials. This work aimed to evaluate the effect of the extractive solution on the starch isolation Ramon seed flour; for that, distilled water (S1) and NaOH solution (S2) were used. The Ramon starch yield was 28.0 ± 1.4% and 31.9 ± 1.7% for S1 and S2. The morphology of starches was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…The CS film presented three T dmax (199, 309 and 325 °C), while BCh (185 and 242 °C), RS (206 and 322 °C), and CCh (204 and 276 °C) films presented two T dmax . The T dmax of the RS and CS films are similar to those reported for Ramon starch [ 41 ] and corn starch [ 51 ] biopolymers, respectively. Based on previous results for BCh and RS films, blends of these biopolymers may result in films with improved thermal properties.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The CS film presented three T dmax (199, 309 and 325 °C), while BCh (185 and 242 °C), RS (206 and 322 °C), and CCh (204 and 276 °C) films presented two T dmax . The T dmax of the RS and CS films are similar to those reported for Ramon starch [ 41 ] and corn starch [ 51 ] biopolymers, respectively. Based on previous results for BCh and RS films, blends of these biopolymers may result in films with improved thermal properties.…”
Section: Resultssupporting
confidence: 82%
“…TGA was performed to evaluate the thermal stability of the chitosan, starch, and composite chitosan-starch- blend films for their application in the food and pharmaceutical industry; during their preparation, processing, or consumption, the films may be subjected to heat processes [ 60 ]. The well-defined peak in the DTGA curve of the starches is related to a reaction mechanism for the degradation of starch biopolymers (amylose and amylopectin) [ 18 , 41 ]. The biological and commercial chitosan films showed significant weight loss from 200 to 500 °C, which is attributed to the pyrolytic decomposition of the saccharide ring dehydration and polysaccharide depolymerization [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type A starches have two strong diffraction peaks around 2θ at about 15 • and 23 • and a doublet around 2θ at 17 • and 18 • , while type B starch possesses a strong diffraction peak around 2θ near 17 • , as well as small peaks around 2θ near 15 • and 24 • . Diffractogram obtained for colok (Talisia floresii starch is similar to that reported by other authors corresponding to ramon (Brosimum alicastrum) [59] and huaya (Melicoccus bijugatus) [25]. The percentage of crystallinity obtained for the starch analyzed in this work was 32 ± 1%.…”
Section: X-ray Diffractionsupporting
confidence: 88%
“…In starches, an amorphous and a crystalline region coexists; the amount of each one of them is important in order to predict the response of this polysaccharide when it is processed, and to identify its behavior when it is stored [13]. In this sense, several authors [13,59,60] have reported the relationship between the bands around 1047 cm −1 referred to the ordered region and the band around 1022 cm −1 referred to the amorphous region. The relationship between these bands represents the order in the starches [59], in the case of the starch obtained from the seeds of colok (Talisia floresii Standl) is 1.7.…”
Section: Fourier Transform Infrared (Ftir) Analysismentioning
confidence: 99%